Minitexts of poetic titles as markers of the English cognitive paradaigm - Yuliya V. Vedeneva; Antonina A. Kharkovskaya; Victoria L. Malakhova (Peoples' Friendship University of Russia (RUDN University), 2018)
Minitexts are of interest to scholars due to the 'shrinking' trend in communication which affects not only language products but also the human mental structures generating them. The correlation of these two planes of human interaction as reflected in minitexts presents a challenge for linguistics. A minitext is viewed as a text of limited length (up to 600 words). The present paper reveals cognitive, pragmasemantic and discursive aspects of minitexts, exemplified by the titles of children's poems. The authors characterise the basic features of such texts (cohesion, coherence, wholeness, intentionality, etc.) and present their thematic typology. The analysis shows that adequate assessment of the identifying markers within poetic minitexts depends on the interaction of text discursive parameters, on the one hand, and their location in the hierarchy of other signs or markers, on the other. Choosing titles for English poems addressed to children, the authors focus on the unusual linguistic units involved in the creation of the titles' artistic imagery and aesthetic effect. One of the evident advantages of the cognitive and pragmatic approach is that it illustrates how minitexts can be useful in developing children's world perception, as well as their artistic tastes.